Simbol Relegius Spiritual dalam Film “Titip Surat Untuk Tuhan” Analisis Semiotika Roland Barthes - Dinar Thahira Handatika; Salma Rosyida Nur Hanifah; Ulul Fadli Zakiyatul Badriyah (STIKes Ibnu Sina Ajibarang, 2026)
This study aims to analyze the religious and spiritual symbols represented in the film Titip Surat untuk Tuhan through Roland Barthes’ semiotic approach, focusing on the three levels of meaning: denotation, connotation, and myth. The research employs a qualitative descriptive method using semiotic analysis based on document studies of selected scenes, dialogues, and visual elements portraying religious values, prayer, sacrifice, patience, hope, gratitude, and trust in God. The findings reveal that symbols such as the mosque, mukena, sarong, prayer mat, the Qur’an, prayer activities, the post office as a medium for sending letters to God, and the calligraphy of “Allah” and “Prophet Muhammad” on the walls function not only as literal signs but also convey profound religious and spiritual connotations. These symbols further develop into myths that reinforce religious norms and cultural beliefs accepted as natural within society. The film successfully constructs a subtle yet powerful representation of faith by portraying a Muslim family that upholds devotion, moral values, patience, compassion, and an enduring relationship with God. Overall, the film demonstrates how religious symbols effectively communicate spiritual messages while strengthening viewers’ understanding of Islamic values through visual and narrative storytelling.